Surrended before the guaria morada - Orozco Abarca, Sergio (2020)
Received: 10-14-2019 Approved: 11-29-2019 ABSTRACT  This article elaborates a study about the "guaria morada", the national symbol of Costa Rica. To do this, it makes a historical approach to orchids, which begins in the fourth century BC, approximately, when the species was baptized, continues with the analysis of the eighteenth century period in which they become a trend in the European market, followed by the moment of his discovery of the "guaria morada" in the jungles of Guatemala, and culminates with the discovery of the plant in Costa Rica. Besides, an analysis of the name "guaria morada" is outlined, and a series of fascinating chronicles regarding different guards are presented. To honor this icon that safeguards in memory as a constituent part of being Costa Rican.